The Scent of Rain and Lightning - Pickard, Nancy (New York : Ballantine Books, 2010)
The man convicted of murdering Jody's father, Billy Cosby, is being released from prison and returning to the small town of Rose, Kansas. Crosby has been granted a new trial, thanks in large part to the efforts of his son, Collin, a lawyer who has spent most of his life trying to prove his father's innocence. As Jody revisits old wounds, startling revelations compel her to uncover the dangerous truth about her family's tragic past.
Keywords: Murder victims' families -- Fiction; Family secrets -- Fiction; Ex-convicts -- Fiction; City and town life -- Fiction -- Kansas; Fiction